EDTA tubes are suitable for insulin and C-peptide measurement in resource-limited settings and can be stored at room temperature for up to 24 hours. - Nathan Mubiru; Rogers Mukasa; Isaac Sekitoleko; Priscilla A Balungi; Ronald M Kakumba; Terry Ongaria; Hubert Nkabura; Moffat Nyirenda; Anxious J Niwaha; Wisdom P Nakanga (PLoS ONE, 2025)
Introduction Insulin and C-peptide assessment are important in characterization and management of diabetes. However, their adoption and increased clinical use in low resource settings (LRSs) is partly hindered by logistical factors including supplies required for pre-analytical sample handling and limited infrastructure. We aimed to determine the effects of altered sample processing conditions on stability of insulin and C-peptide at the pre-analytical stage. Methods Random (non-fasted) blood samples were drawn from ten healthy (glucose range 4.1-8.0 mmol/L) participants. We investigated the mean % change from baseline of C-peptide and insulin in serum (plain tubes) vs plasma (K2EDTA tubes), centrifuged vs uncentrifuged, room vs cool box temperature on the stability of C-peptide and insulin up to 24 hours using Wilcoxon signed rank test. Results were considered clinically significant if the percentage change was > 10% and if the p-value was < 0.05. Results Eight patients were included in the final analysis, while two were excluded due to hemolysis. C-peptide and insulin levels stayed above 90% of the baseline concentration in K2EDTA tubes across all storage and processing conditions for up to 24 hours. In contrast, samples collected in plain serum tubes kept at room temperature and uncentrifuged, C-peptide and insulin levels decreased significantly to 51% (p = 0.006) and 62% (p = 0. 083) respectively, similarly insulin levels for centrifuged samples declined to 64% (p = 0.083). All iced and centrifuged serum samples remained above 90% of baseline concentration. Conclusions In resource-limited settings where insulin and C-peptide tests are limited to central laboratories and highly dependent on sample referral systems, these tests can be reliably measured without the need for immediate centrifugation or processing from samples collected in whole blood K2EDTA tubes uncentrifuged kept at room temperature and processed within 24hours.